Peran Hukum dalam Mendorong Pembangunan Ekonomi dan Menjamin Kesejahteraan Masyarakat : Perspektif Indonesia - Bahrul Ulum (Lembaga Pengembangan Kinerja Dosen, 2025)
This article examines the important role of law in promoting economic development and ensuring the well-being of people in Indonesia. It analyzes the legal framework that governs economic activities, focusing on principles and regulations that facilitate economic growth, protect rights, and promote social justice. This article explores the evolution of Indonesia's legal system in response to economic challenges and opportunities, highlighting key laws and policies that have shaped the nation's economic landscape. This includes an analysis of the constitutional foundations of Indonesia's economic system, with a special emphasis on Article 33 of the 1945 Constitution, which mandates a